Human rights collectives as visual experts: the case of Syrian Archive. (August 2019) - Ristovska, Sandra
This article maps the institutional context that renders eyewitness video meaningful for human rights purposes. By looking closely at the work of Syrian Archive, this article argues that human rights collectives are positioning themselves as visual experts that both mimic established institutional modalities and help offset the lack of replicable workflows and clear visual standards for eyewitness video across journalism, the law and political advocacy. In doing so, this article illuminates the larger information networks that characterize the production, circulation and legitimacy of human rights videos today.